The effect of different agar media and combinations on the mycelium growth periods of Pleurotus djamor (Rumph. Ex Fr.) Boedijn and Pleurotus citrinopileatus Singer mushrooms - Kırbağ, Sevda; Yılmaz, Didem; Gezici, Yusuf (Mehmet ÖZASLAN, 2026)
Mushrooms are a food preferred by humans due to their rich nutritional content and are available as both wild and cultivated mushrooms. In cultivated mushroom production, rapid mycelium growth is desirable. Mycelium can be obtained quickly using different agar media. This study aimed to determine the growth of Pleurotus djamor and Pleurotus citrinopileatus mycelia in different agar media and media combinations and to identify the species that showed the fastest and most efficient growth. Mycelia were placed in pure and mixed agar media and left to incubate, and mycelial growth areas were measured at daily intervals. Although the nutrient agar media differed, MEA and PDA were determined to be the best mycelium growth media for P. djamor and P. citrinopleatus in terms of mycelium growth time. This study has revealed the mycelial growth periods of P. djamor and P. citrinopileatus in different agar media, and it is anticipated that it will contribute to spawn preparation and culture conditions.
Tübitak (2209-a, 2021-2 no:19198012107094
Keywords: P. djamor; P. citrinopleatus; nutrient medium; mycelial growth period; culture mushroom